Pemikiran Ibnu Taimiyyah tentang Integrasi Nilai Agama dan Intelektual dalam Pendidikan Islam di Indonesia - Nur Hakim; Muhammad Aji Nugroho (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
Abstract This research aims to analyze Ibn Taimiyyah's thoughts on the integration of religious and intellectual values ​​in Islamic religious education in Indonesia. The research approach uses a qualitative approach with the type of library research. The data collection technique is through reviewing literature books, academic journals, notes and scientific reports, then the data is analyzed in depth, carefully, objectively and systematically through the use of descriptive data analysis techniques, namely by reducing, presenting the data and then drawing conclusions. . Research findings show that Ibn Taymiyyah's thoughts on the integration of religious and intellectual values ​​are very relevant for Islamic education in Indonesia today. He emphasized the importance of synergy between revelation and reason to form humans who are knowledgeable and have noble character. Its relevance lies in the need for a curriculum that combines monotheism, Islamic ethics and critical thinking skills, in order to create a generation that is intellectually intelligent and has moral commitment. This integration-based holistic education paradigm is a solution in facing the challenges of modern education in Indonesia. By adopting Ibn Taymiyyah's thoughts on the integration of religious and intellectual values, the Islamic education system in Indonesia can present a new paradigm that answers the needs of the times without losing its spiritual roots. This integration is a strategic step to face the challenges of educational modernization while maintaining a strong Islamic identity and being adaptive to global changes.